THE APPLICATION OF THE CONTEXTUAL TEACHING AND LEARNING MODEL IN INCREASING LEARNING MOTIVATION IN THE SUBJECT OF ISLAMIC CULTURAL HISTORY AT THE ISLAMIC JUNIOR HIGH SCHOOL OF SUBULUS SALAM - Nurfela; Sriwardona (Amanah Publishing, 2025)
Teaching and learning in Islamic Cultural History is ineffective because teachers lack a thorough understanding of the components and steps within the Contextual Teaching and Learning model. Students are lacking motivation to learn, and obstacles persist in the learning process, such as students being preoccupied with their own activities, talking with their deskmates, sleeping, limited time, and students' lack of participation in the learning process. The objectives of this study are: 1) to determine the application of the Contextual Teaching and Learning learning model, 2) to determine the supporting factors, 3) to determine the inhibiting factors in improving learning motivation in Islamic Cultural History at the Islamic Junior High School of Subulus Salam. This study uses a descriptive approach. The type of research conducted by the author is field research, namely descriptive qualitative field research, which is a study that describes the application of the Contextual Teaching and Learning learning model in improving learning motivation in Islamic Cultural History at Islamic Junior High School of Subulus Salam. The data sources used are primary and secondary data, such as interviews, observations, and direct field documentation. Informants in this study were Islamic Cultural History teachers, students, and the principal. To analyze this data, data reduction was used. The author used data triangulation and source triangulation to present the data. Based on the results of this study, it can be concluded that: 1) The implementation of the Contextual Teaching and Learning learning model involves planning, namely the inclusion of the Contextual Teaching and Learning model in the lesson plan). The implementation of this Contextual Teaching and Learning learning model is in accordance with the components and steps, but is not optimal and still faces obstacles. Evaluation through reflection and assessment is necessary. 2) Supporting factors for the use of the Contextual Teaching and Learning learning model include collaboration between teachers and students, adequate learning media, and a supportive environment for applying the material to students' daily lives. 3) Inhibiting factors for the use of the Contextual Teaching and Learning learning model include limited time, teachers only having general knowledge of the Contextual Teaching and Learning learning model, and a lack of student creativity.